2016
DOI: 10.7717/peerj.1724
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variants in the MicroRNA biosynthetic pathway Gemin3 and Gemin4 are associated with a risk of cancer: a meta-analysis

Abstract: The effects of the microRNA (miRNA) processing genes Gemin3 and Gemin4 on cellular signaling pathways could have a major impact on the risk of cancer. Several studies concerning the association between the Gemin3 rs197412, Gemin4 rs7813 and Gemin4 rs2740348 polymorphisms with cancer susceptibility have been published. The present meta-analysis summarized this evidence and evaluated the precision of these relationships. Relevant studies (published prior to December 16th, 2015) without language restriction were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 35 publications
1
14
1
Order By: Relevance
“… 26 , 27 More interestingly, Yang et al found that a haplotype of the GEMIN4 gene including rs2740348 was associated with increased risk of bladder cancer. 31 In our present meta-analysis, we found that rs2740348 was significantly associated with increased risk of cancer in the general population under the recessive model (GG vs GC/CC), which agreed with the result reported by Zhu et al 35 However, this conclusion was only confirmed in a mixed population, but not in Asians and Caucasians. Therefore, the discrepancy of the results might be partly attributed to the difference of the study population.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“… 26 , 27 More interestingly, Yang et al found that a haplotype of the GEMIN4 gene including rs2740348 was associated with increased risk of bladder cancer. 31 In our present meta-analysis, we found that rs2740348 was significantly associated with increased risk of cancer in the general population under the recessive model (GG vs GC/CC), which agreed with the result reported by Zhu et al 35 However, this conclusion was only confirmed in a mixed population, but not in Asians and Caucasians. Therefore, the discrepancy of the results might be partly attributed to the difference of the study population.…”
Section: Discussionsupporting
confidence: 92%
“… 24 , 32 In the present study, we reported that rs7813 was related to an increased risk of cancer in the general population under the recessive model (TT vs TC/CC), but this conclusion was only confirmed in Asians, not in Caucasians, which is contrary to a previous meta-analysis. 35 Thus, we inferred that the discrepancy might be explained by the diversity of study population and tumor types.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…The role of GEMIN4 protein in miRISC is not very clear. Aberrant microRNA biosynthesis genes have been found to be implicated in the genesis, development and survival of several types of cancer, indicating that a more general role may exist in microRNA biosynthesis genes in modifying the development of cancer [15,16,18,19,20,31,32]. While the underlying associations by which microRNA biosynthesis genes influences the risk of lung cancer remains unclear, our findings provide strong evidence regarding the association between SNPs in microRNA biosynthesis genes and lung cancer risk.…”
Section: Discussionmentioning
confidence: 99%
“…MicroRNAs have been confirmed to be involved in most of the human biological processes at the posttranscriptional level; deregulation of microRNA is considered to be involved in human cancer [7,8,9,10]. The abnormality of microRNA biosynthesis genes can affect the regulatory effect of global microRNAs to target mRNA, thereby influencing diseases; therefore, the abnormality of microRNA biosynthesis genes may play an important part in human cancer [11,12,13,14,15]. …”
Section: Introductionmentioning
confidence: 99%